Tellurium and Selenium Mineralogy of Gold Deposits in Northern Fennoscandia - Arkadii Kalinin (Minerals, 2021)
Mineralization of Te and Se was found in gold deposits and uranium occurrences, located in the Paleoproterozoic greenstone belts in Northern Fennoscandia. These deposits are of different genesis, but all of them formed at the late stages of the Svecofennian orogeny, and they have common geochemical association of metals Au, Cu, Co, U, Bi, Te, and Se. The prevalent Te minerals are Ni and Fe tellurides melonite and frohbergite, and Pb telluride altaite. Bismuth tellurides were detected in many deposits in the region, but usually not more than in two–three grains. The main selenide in the studied deposits is clausthalite. The most diversified selenium mineralization (clausthalite, klockmannite, kawazulite, skippenite, poubaite) was discovered in the deposits, located in the Russian part of the Salla-Kuolajarvi belt. Consecutive change of sulfides by tellurides, then by selenotellurides and later by selenides, indicates increase of selenium fugacity, fSe2, in relation to fTe2 and to fS2in the mineralizing fluids. Gold-, selenium-, and tellutium-rich fluids are potentially linked with the post-Svecofennian thermal event and intrusion of post-orogenic granites (1.79–1.75 Ga) in the Salla-Kuolajarvi and Perapohja belts. Study of fluid inclusions in quartz from the deposits in the Salla-Kuolajarvi belt showed that the fluids were high-temperature (240–300 °C) with high salinity (up to 26% NaCl-eq.). Composition of all studied selenotellurides, kawazulite-skippenite, and poubaite varies significantly in Se/Te ratio and in Pb content. Skippenite and kawazulite show the full range of Se-Te isomorphism. Ni-Co and Co-Fe substitution plays an important role in melonite and mattagamite: high cobalt was detected in nickel telluride in the Juomasuo and Konttiaho, and mattagamites from Ozernoe and Juomasuo contain significant Fe. In the Ozernoe uranium occurrence, the main mineral-concentrator of selenium is molybdenite, which contains up to 16 wt.% of Se in the marginal parts of the grains. The molybdenite is rich in Re (up to ...